Note on distances of posets whose double bound graphs are the same - Ogawa, Kenjiro; Tsuchiya, Morimasa (Utilitas Mathematica, 2005)
In this paper, we consider transformations between posets P and Q, whose double bound graphs are the same. We obtain some properties on distances of posets, which have the same double bound graph. Furthermore we determine the maximum distance of posets.